Investigating how movement affects prey camouflage using an insect predator - Umeton, Diana; Canonaco, Marcello; Brandmayr, Pietro (My University, 2019)
Patterns that help prey camouflage themselves whilst stationary prove to be ineffective once prey move. Given that motion breaks camouflage, can a moving prey ever be effectively concealed? Recent studies have found that certain patterns might help prey deceive their predators whilst moving, as in the case of ‘motion dazzle’. However, research with moving prey has been conducted using only humans or birds as predator models, and consequently, it is now known how other predator species might behave. In addition, it is important to know not just how motion affects camouflage, but also how the speed of motion can affect the efficacy of different defensive patterns. This thesis aims to address these current gaps in the field. First, I explore the visual acuity in a group of insect predators, the praying mantids, to explore if different species vary in their visual acuity, which could impact on what they can perceive and which selective pressure they could exert on prey defensive patterns. Second, using praying mantids tracking computer-generated stimuli, I empirically investigate how cryptic and conspicuous patterns might enhance the survival of moving prey. In particular, I specifically investigate if high contrast striped prey could reduce predation risk through the visual phenomenon known as “flicker fusion effect”. I found that when prey were slow moving, all patterns were equally detectable by the mantids. However, once prey moved at faster speed, a cryptic pattern was more likely to be tracked than a more conspicuous black-and-white striped pattern suggesting that the latter was successful in inducing flicker fusion effect in praying mantids’ eyes. This thesis starts to disentangle how pattern and speed could combine to help camouflage an animal when moving through its environment. The outcome of the study are discussed in the wider context of how animals coloration and behaviour evolved together to confer them survival advantages.
Dottorato di Ricerca in Scienze della Vita. Ciclo XXIX
Keywords: Camouflage; Praying mantis